2011
DOI: 10.1038/bjc.2011.349
|View full text |Cite
|
Sign up to set email alerts
|

Rapid non-genomic signalling by 17β-oestradiol through c-Src involves mTOR-dependent expression of HIF-1α in breast cancer cells

Abstract: Background:Hypoxia-inducible factor 1 (HIF1) has been implicated in regulating many of the genes responsible for angiogenesis, erythropoiesis, glucose metabolism and cancer pathogenesis. In this study, we demonstrate that exposure of human breast cancer lines to 17β-oestradiol (E2) rapidly induced the expression of HIF-1α, the regulated subunit of HIF1, in normoxic condition. Hypoxia-inducible factor-1α is normally degraded in normoxia through ubiquitination-mediated proteolysis, whereas hypoxia modulates HIF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 32 publications
1
34
0
Order By: Relevance
“…HIF-1a induction in malignant cells is closely linked to PI3K/Akt and mTOR signaling (27)(28)(29), which are frequently involved in cancer cell proliferation, metabolism, and survival (30). In breast cancer cells, estrogen-induced HIF-1a accumulation was shown to occur through the PI3K/Akt pathway leading to mTOR phosphorylation (31). In our results, resveratrol reduced activated Akt levels in LLC cells in a manner that preceded suppression of HIF-1a accumulation.…”
Section: Discussionsupporting
confidence: 53%
“…HIF-1a induction in malignant cells is closely linked to PI3K/Akt and mTOR signaling (27)(28)(29), which are frequently involved in cancer cell proliferation, metabolism, and survival (30). In breast cancer cells, estrogen-induced HIF-1a accumulation was shown to occur through the PI3K/Akt pathway leading to mTOR phosphorylation (31). In our results, resveratrol reduced activated Akt levels in LLC cells in a manner that preceded suppression of HIF-1a accumulation.…”
Section: Discussionsupporting
confidence: 53%
“…Despite the classical mode of action of estradiol, it has been implicated in a rapid non-genomic signaling cascade involving ER interaction with the non-receptor tyrosine kinase c-Src, which activates the phosphatidylinositol-3 kinase/Akt pathway [9]. It has also been reported that c-Src is an important adapter protein between extranuclear ERs and HER2, allowing for cross talk pathways in cancer cell lines [10].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, E 2 and growth factors/growth factor receptors can result in phosphorylation of ERα at Ser118 by MAPK, thus linking rapid, membrane-initiated, non-genomic ERα responses with later bona fide ERα genomic actions. [14][15][16][17][18][19] Because the genomic and non-genomic actions of ERα are complementary and even synergistic via crossregulatory interactions that are mediated through cross-talk with other growth factor and cellular signal transduction pathways, the fact that the SOX2-driven reprogramming of breast CSC-like states was involved in the derepression of the phospho-Ser118-ERα-activating insulin receptor/mTOR pathway 4 strongly suggested that the E 2 -hypersensitive phenotype of the SOX2-overexpressing MCF-7/ Rep xenotumors might be explained in terms of increased phospho-Ser118-ERα. When testing the hypothesis that phosphoSer118-ERα levels might correspond to enhanced estrogenic responses and tumorinitiating ability in SOX2-overexpressing MCF-7/Rep cells, we first observed that the basal protein expression of ERα, which was diffusely distributed throughout the cytoplasm and nucleus, was increased in SOX2-overexpressing CSC-like MCF-7/ Rep cells compared with MCF-7 parental cells (Fig.…”
Section: T He Restoration Of Pluripotency Cir-mentioning
confidence: 99%